2018
DOI: 10.1093/asj/sjy037
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Contraction in Body Contouring With Radiofrequency-Assisted Liposuction: A Treatment Gap Solution

Abstract: Radiofrequency-assisted liposuction is a relatively new concept in energy-assisted body contouring techniques and has received instrument approval. This supplemental article reviews the clinical application of electromagnetic energy via the BodyTite (InMode Corporation, Toronto, Canada) device on soft tissues during suction lipectomy, its effect on soft tissue contraction, and its use in aesthetic body contouring in various clinical scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…Theodorou et al described near circumferential (270 degrees) RF-assisted liposuction of the upper arms in 40 patients. 3,4 An objective plastic surgeon evaluated the results as good to excellent tightening of the soft tissue envelope in the majority of patients. There were minimal complications in this cohort (1 seroma resolved with aspiration and 1 burn treated with wound care).…”
Section: Examples Of Clinical Applications Of Rf Microneedlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Theodorou et al described near circumferential (270 degrees) RF-assisted liposuction of the upper arms in 40 patients. 3,4 An objective plastic surgeon evaluated the results as good to excellent tightening of the soft tissue envelope in the majority of patients. There were minimal complications in this cohort (1 seroma resolved with aspiration and 1 burn treated with wound care).…”
Section: Examples Of Clinical Applications Of Rf Microneedlingmentioning
confidence: 99%
“…For example, fat is an insulator and has high resistance to current flow (producing more heat), and water is closest to a pure conductor (producing less heat). 4,16 New collagen, elastin, and blood vessel formation occurs as skin surface temperatures reach 40° to 45°C. 1,2,17-19 In contrast to laser, RF is chromophore independent and has a better safety profile for all skin types in terms of pigmentation changes.…”
mentioning
confidence: 99%
“…Although this heat is targeted between the 2 electrodes, monopolar devices are believed to lead to a more uniform volumetric heating. Theodorou et al 37 reported outcomes on 40 patients undergoing bipolar RF-assisted liposuction (Bodytite; InMode, Lake Forest, Calif.) without any major complications and 2 minor complications, including a superficial burn and a seroma that resolved with aspiration. Patient satisfaction was high at 6 months, with >90% of patients satisfied to extremely satisfied.…”
Section: Radiofrequency Delivery: Monopolar Bipolar Rf Delivery Andmentioning
confidence: 99%
“…A recent corporate-funded supplemental article, written by surgeons who are also shareholders, claims that radiofrequency-assisted liposuction (BodyTite, InMode Corp., Toronto, Canada) provides effective soft-tissue contraction, even creating an “internal brachioplasty scar.” 37 This claim is based on a greater reduction in linear measurements than area measurements after radiofrequency-assisted liposuction compared with standard liposuction, a finding that is impossible to reconcile with basic geometry (the difference in area measurements must exceed linear changes). 38 The authors offer a favorable return on investment analysis to justify the $205,000 purchase price, based on a $7,000 treatment fee.…”
Section: Examples Of Conflict Of Interest In Plastic Surgerymentioning
confidence: 99%
“…38 The authors offer a favorable return on investment analysis to justify the $205,000 purchase price, based on a $7,000 treatment fee. 37…”
Section: Examples Of Conflict Of Interest In Plastic Surgerymentioning
confidence: 99%